2007
DOI: 10.1101/lm.627007
|View full text |Cite
|
Sign up to set email alerts
|

Control of appetitive and aversive taste-reactivity responses by an auditory conditioned stimulus in a devaluation task: A FOS and behavioral analysis

Abstract: Through associative learning, cues for biologically significant reinforcers such as food may gain access to mental representations of those reinforcers. Here, we used devaluation procedures, behavioral assessment of hedonic taste-reactivity responses, and measurement of immediate-early gene (IEG) expression to show that a cue for food engages behavior and brain activity related to sensory and hedonic processing of that food. Rats first received a tone paired with intraoral infusion of sucrose. Then, in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 44 publications
7
65
2
Order By: Relevance
“…Furthermore, the performance of control rats that received the two CSs unpaired with the US indicated that the shift in response form we observed with extended training in the other groups did not reflect habituation of unconditioned positive responses to the auditory CSs or some other nonassociative factor. Our results also differed somewhat from those of Kerfoot et al (2007). First, here we found no evidence for the auditory CS's control over TR responses until after the unflavored water substrate was provided (CS + water or post-CS periods), whereas Kerfoot et al (2007) observed low but significant levels of such control during CS presentations even before presentation of the water substrate.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the performance of control rats that received the two CSs unpaired with the US indicated that the shift in response form we observed with extended training in the other groups did not reflect habituation of unconditioned positive responses to the auditory CSs or some other nonassociative factor. Our results also differed somewhat from those of Kerfoot et al (2007). First, here we found no evidence for the auditory CS's control over TR responses until after the unflavored water substrate was provided (CS + water or post-CS periods), whereas Kerfoot et al (2007) observed low but significant levels of such control during CS presentations even before presentation of the water substrate.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results also differed somewhat from those of Kerfoot et al (2007). First, here we found no evidence for the auditory CS's control over TR responses until after the unflavored water substrate was provided (CS + water or post-CS periods), whereas Kerfoot et al (2007) observed low but significant levels of such control during CS presentations even before presentation of the water substrate. Second, we found no evidence of spontaneous transfer of the aversive TR response established to sucrose itself during devaluation training in Group Devalue, to either auditory CS.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We assessed hedonic impact further by measuring orofacial reactions to the Pavlovian CS+ cues, which in principle, can acquire conditioned hedonic value as well as incentive value from their paired UCS (55)(56)(57)(58)(59)(60). The CS+1 tone occasionally and the CS+2 more frequently elicited a few positive hedonic reactions (on average, 1 reaction per 10 s under vehicle condition; this weak hedonic conditioned response was only 12% of the UCS unconditioned level of 8.3 per 10 s, but tone-elicited reactions were still mildly elevated over near-zero pre-CS baseline levels; CS+2: F 1,157 = 8.30, P < 0.01; CS+1: F 1,157 = 3.82, P = 0.052) (Fig.…”
Section: Nac Opioid Stimulation But Not Dopamine Accentuates Palatabimentioning
confidence: 99%